2014
DOI: 10.1177/0284185113493775
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy with peritumoral injection versus lymphoscintigraphy with subdermal periareolar injection of technetium-labeled human albumin to identify sentinel lymph nodes in breast cancer patients

Abstract: Background: Preoperative lymphoscintigraphy is without doubt a valid method for the detection of the sentinel lymph node (SLN). There has been considerable debate regarding the optimal site for the introduction of the tracer; various sites include peritumoral (PT), periareolar (PA), subdermal, and intradermal injection. Purpose: To evaluate retrospectively the lymphoscintigraphic identification rate of peritumoral (PT) injection versus subdermal periareolar (PA) injection in the detection of SLNs in breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
(34 reference statements)
0
31
0
Order By: Relevance
“…There remains considerable debate about the different drainage patterns. Large differences between the drainage patterns from the different sites were recently reported in a small study, 32 while Caruso et al 33 concluded that the same SLNs were reached from different injection sites. In our study, the SLNs identified during surgery were both magnetic and hot in all but one patient, indicating similar drainage patterns, and thus supporting the conclusion drawn by Caruso.…”
Section: Discussionmentioning
confidence: 89%
“…There remains considerable debate about the different drainage patterns. Large differences between the drainage patterns from the different sites were recently reported in a small study, 32 while Caruso et al 33 concluded that the same SLNs were reached from different injection sites. In our study, the SLNs identified during surgery were both magnetic and hot in all but one patient, indicating similar drainage patterns, and thus supporting the conclusion drawn by Caruso.…”
Section: Discussionmentioning
confidence: 89%
“…These 18 studies underwent full‐text review and one further study was excluded from the systematic review on the basis of the absence of a preoperative diagnosis of invasive or in situ malignancy. Of the 17 studies remaining, another four were excluded from the meta‐analysis because there was no comparison of superficial versus deep injections of radiotracer with or without blue dye. Thus a total of 13 studies met the inclusion criteria for meta‐analysis ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…These six patients all had successful SLNB with 100 per cent SLN identification. Pelosi et al 34 26 Mateos et al 30 Maza et al 31 Mudun et al 32 Noushi et al 16 Rodier et al 35 Roumen et al 17 Shimazu et al 36 Uren et al 13 Total Heterogeneity: τ 2 = 0·74; χ 2 = 37·64, 8 d.f., P < 0·001; I 2 = 79% Test for overall effect: Z = 1·31, P = 0·19 24 Fowler et al 15 3 of 339 1 of 15…”
Section: Different Superficial Injections Of Radioactive Tracer With mentioning
confidence: 97%
See 1 more Smart Citation
“…Several other reports have stated that SLN identification is not affected by the injection site regardless of whether the injection is intranipple or peritumoral (Kern 2001 ; Caruso et al. 2014 ; Rosenow et al. 2012 ).…”
Section: Discussionmentioning
confidence: 98%